Antioxidant and antimicrobial activities of Hyptis suaveolens essential oil - Witayapan Nantitanon (2018)
The essential oil of Hyptis suaveolens obtained by steam distillation was examined for its antioxidant and antimicrobial activities. The antioxidant activity was determined by means of the DPPH radical scavenging test and ABTS free radical decolorization assay. Results from both methods indicate that the antioxidant activity of H. suaveolens oil is time and concentration dependent. The antioxidant potential of H. suaveolens oil determined by the DPPH method expressed as IC 50 was 3.72 mg/ml whereas the TEAC value determined by the ABTS assay was 65.02 μM/mg. The antimicrobial activity of the essential oil was assessed by the dilution and well diffusion methods. The results show that the antifungal potential of H. suaveolens oil is more pronounced than its antibacterial properties. Its fungal growth inhibitory activity was dose dependent with a MID value of 1:640. The 20% ethanolic solution of H. suaveolens oil had antifungal power similar to 6% boric acid, 2% benzoic acid, or 5% salicylic acid but higher than 4% phenol. The activity decreased when the oil was stored at high temperature (> 40°C). The results of GC-MS analysis indicated the changes in oil composition which led to the decrease in antifungal activity. © Österreichische Apotheker-Verlagsgesellschaft m. b. H.